2001
DOI: 10.1186/bcr306
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cell kinetics in breast carcinogenesis

Abstract: IntroductionTissue homeostasis is maintained through a balance between cell proliferation and apoptosis. Both are active processes that are influenced by a wide variety of regulatory stimuli. Each cell is under constant surveillance in order to maintain the integrity of its genome. When onco-AI = apoptotic index; FITC = fluorescein isothiocyanate; P/A index = proliferative index/apoptotic index; PI = proliferative index; TUNEL = TdT-mediated dUTP-nick end-labelling.Available online http://breast-cancer-researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 39 publications
1
7
0
3
Order By: Relevance
“…The apoptotic indices reported by these authors vary by an order of magnitude (0.1 to 1.2), compared with 0.3 reported in another study where morphology alone was used to identify apoptotic cells (Potten et al 1988). Studies using TUNEL report values ranging from 0.0 (Bai et al 2001) to 0.04 (Wong et al 2001), to 2.1 per terminal duct lobular unit (Feuerhake et al 2003). Using TUNEL, we have found values of 0.2% for premenopausal women, and 0.1% for postmenopausal women.…”
Section: Apoptosis In Normal Breast Epitheliummentioning
confidence: 83%
See 1 more Smart Citation
“…The apoptotic indices reported by these authors vary by an order of magnitude (0.1 to 1.2), compared with 0.3 reported in another study where morphology alone was used to identify apoptotic cells (Potten et al 1988). Studies using TUNEL report values ranging from 0.0 (Bai et al 2001) to 0.04 (Wong et al 2001), to 2.1 per terminal duct lobular unit (Feuerhake et al 2003). Using TUNEL, we have found values of 0.2% for premenopausal women, and 0.1% for postmenopausal women.…”
Section: Apoptosis In Normal Breast Epitheliummentioning
confidence: 83%
“…The measurement of apoptosis in the normal breast has been performed by the counting of apoptotic bodies on histological sections, by the TUNEL (TdT-mediated dUTP nick-end labeling) reaction, and more recently by IHC detection of activated caspase-3, which represents the final enzymatic event leading to DNA fragmentation (Gown & Willingham 2002). There is agreement that a wave of apoptosis occurs in late luteal phase (Anderson et al 1982, Williams et al 1991, and that proliferative and apoptotic rates increase as epithelium progresses from normality to malignancy (Allan et al 1992, Bai et al 2001. Two studies of apoptosis and proliferation in normal breast epithelium from women with breast cancer and those undergoing benign breast biopsy for conditions such as fibroadenoma concluded that the ratio of proliferative to apoptotic indices is higher in women with breast cancer (Allan et al 1992, Hassan & Walker 1998, suggesting that decreased elimination of epithelial cells may contribute to the development of malignancy.…”
Section: Apoptosis In Normal Breast Epitheliummentioning
confidence: 99%
“…For example, it has been widely observed that, in breast cancer, the rates of proliferation and cell death are positively correlated [58-61]. Apoptosis and necrosis are associated with both enhanced lymphocytic infiltrate in breast cancer [60] and enhanced immunogenic response [62-64].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, the scenarios delineated above are difficult to reconcile with the significant spontaneous apoptosis rates observed in several human tumor types which often exceed those of corresponding normal tissues [138,139,140,141,142,143,144,145,146,147,148,149]. In fact, spontaneous apoptosis occurring in malignant neoplasms was already noted in the seminal publication of Kerr et al (1972) that coined the term apoptosis [150].…”
Section: The Occurrence Of Spontaneous Apoptosis In Tumorsmentioning
confidence: 99%
“…For small cell lung carcinoma an AI of 2.65% (mean) was reported [147], for prostate cancer an AI of 1.9% [148], and for gastric cancer an AI of 1.97% [146]. Several studies on breast cancer have even demonstrated a correlation between the rate of apoptosis and tumor progression [138,139,142]. In one study [138], the AI in breast cancer varied from 0.02% for hyperplasia up to 3.69% for invasive carcinoma (median 1.17%).…”
Section: The Occurrence Of Spontaneous Apoptosis In Tumorsmentioning
confidence: 99%